2012
DOI: 10.1016/j.chemgeo.2011.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties and transformations of precipitated FeS

Abstract: Editor: J. Fein Keywords:Amorphous iron sulfide Mackinawite Greigite Phase transformations XRD TEM Nanocrystalline iron sulfides form in diverse anoxic environments. The initial precipitate is commonly referred to as nanocrystalline mackinawite (FeS) or amorphous FeS. In order to better understand the structure of the initial precipitate and its conversion to mackinawite and greigite (Fe 3 S 4 ), we studied synthetic iron sulfide samples that were precipitated from hydrous solutions near room temperature. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
81
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 45 publications
15
81
2
Order By: Relevance
“…This proposed description of the MMAS is consistent with the graphene and carbon nanotube buckling under stresses or strains [37][38][39][40]. It is also in agreement with observations of wrinkled sheets of ~65-85 nm with central units of semi ordered atomic layer of about 3-8 nm in amorphous FeS [29]. In other words, if the amorphous material were exfoliated to a single atomic layer, one would find a wrinkled layer.…”
Section: First Steps Of a Microstructural Model Of The Amorphous Strusupporting
confidence: 74%
See 1 more Smart Citation
“…This proposed description of the MMAS is consistent with the graphene and carbon nanotube buckling under stresses or strains [37][38][39][40]. It is also in agreement with observations of wrinkled sheets of ~65-85 nm with central units of semi ordered atomic layer of about 3-8 nm in amorphous FeS [29]. In other words, if the amorphous material were exfoliated to a single atomic layer, one would find a wrinkled layer.…”
Section: First Steps Of a Microstructural Model Of The Amorphous Strusupporting
confidence: 74%
“…Wrinkles are commonly observed in natural materials [19,20], on stretched membranes and thin films [21][22][23][24][25][26][27][28], in synthetic materials [28,29], on surface growth of oxides [30] and on the solidified surface of liquid [31]. They typically account for applied strains or stress relaxations in the thin materials.…”
Section: Microstructures Of Wedged and Cylindrical Ingots Of Fe 50 Nimentioning
confidence: 99%
“…The fresh nZVI treated with dithionite also shows a distinguishable peak for zero valent iron and iron (oxy)(hydr)oxides, but with a lower intensity (Figure 3.7b). The weak and broad peak at 20° suggest that iron sulfides have started to form (Jeong et al, 2008, Csakberenyi-Malasics et al, 2012, Fan et al, 2013 shortly (within 30 minutes) after injection of dithionite to the nZVI. It is expected that the amorphous phase of mackinawite (also known as disordered mackinawite or amorphous iron(II) monosulfide, FeS am ) will form first since it is the first iron sulfide formed through the reaction of Fe 2+ and S 2- (He et al, 2010b).…”
Section: Characterization Of Iron Nanoparticlesmentioning
confidence: 99%
“…(1) Gaines et al, 1997;Mackoviky, 2006 (2) Barton and Skinner, 1967 (3) Murowchick and Barnes, 1986b;Schoonen and Barnes, 1991;Rakovan et al, 1995 (4) Hunger andBenning, 2007 (5) Furukawa andBarnes, 1996 (6) Kissin, 1974; note that pyrrhotite is not an ideal solid solution (7) Kissin, 1974(8) Toulmin and Barton, 1964(9) Murowchick and Barnes, 1986a; not found in nature due to its instability (10) Benning et al, 2000b;Rickard, 2012;Csákberényi-Malasics et al, 2012 These phases are also shown in Figure 4 .5, a somewhat simplified diagram, especially for the lower temperatures .…”
Section: Evidence Of Environmental Conditions From Ubiquitous Iron Sumentioning
confidence: 99%